Kesulitan Belajar Matematika Berkaitan dengan Konsep pada Topik Aljabar: Studi Kasus pada Siswa Kelas VII Sekolah ABC Lampung [Difficulties in Learning Mathematics Concepts in Algebra: A Case Study of Grade VII Students in ABC School Lampung] - Eka Wati; Melda J Saragih (Universitas Pelita Harapan, 2018)
Algebra is an important part of Mathematics that Grade 7 students must learn. Students have difficulty learning algebraic concepts at ABC School in Lampung. The purpose of this study is to identify the difficulties experienced by students in learning algebraic conceptss as well as identify factors that affect students who experience difficulties. This research uses a qualitative case study approach focusing on two students in class VII. Data collection techniques consisted of tests, planned unstructured interviews, and student task documentation. The results showed that: (1) students' difficulties in learning mathematics related to the concept were: (a) difficulty in identifying concepts; (b) difficulty using symbols to represent concepts; (c) difficulty in identifying the given conceptual properties and recognizing the conditions specified by a concept; (d) difficulty translating from a presentation model to another presentation mode; (e) difficulty comparing and asserting concepts; and (2) Factors that make it difficult for students are the influence of difficulty on a particular topic and difficulty in abstracting.BAHASA INDONESIA ABSTRAK: Aljabar adalah salah satu bagian penting yang harus dipelajari oleh siswa. Pada kenyataannya masih terdapat kesulitan siswa dalam mempelajari konsep aljabar, seperti yang terjadi di Sekolah ABC Lampung. Tujuan penelitian ini untuk mengidentifikasi kesulitan yang dialami siswa dalam mempelajari matematika topik aljabar serta mengidentifikasi faktor yang mempengaruhi siswa mengalami kesulitan. Penelitian ini menggunakan pendekatan kualitatif studi kasus, subjek 2 siswa kelas VII. Teknik pengumpulan data;tes, wawancara terencana-tidak terstruktur, dan dokumentasi tugas siswa. Hasil penelitian menunjukkan bahwa: (1) kesulitan siswa dalam mempelajari matematika berkaitan dengan konsep antara lain; (a) kesulitan mengidentifikasi konsep; (b) kesulitan menggunakan simbol untuk mempresentasikan konsep; (c) kesulitan mengidentifikasi sifat-sifat konsep yang diberikan dan mengenali kondisi yang ditentukan suatu konsep (d) kesulitan menterjemahkan dari suatu model presentasi ke mode presentasi yang lainnya; (e) kesulitan membandingkan dan menegaskan konsep-konsep; (2) Faktor yang mempengaruhi siswa mengalami kesulitan adalah pengaruh kesulitan pada suatu topik tertentu dan kesulitan dalam mengabstraksi.